Implementasi Program Tahfidzul Qur'an dalam Pengentasan Buta Huruf Al-Qur'an di Sekolah - Yuliasa Wiwaha, Made Gede; Zulfitria, Zulfitria; Wilfridus, Wilfridus (Jurnal Pendidikan Agama Islam, 2024)
This research aims to examine the form of implementation of tahfidzul Al-Qur'an in the context of school education. This research uses a literature study approach on various articles that have been published in national journals with a focus on studying tahfidzul Qur'an and eradicating Qur'an illiteracy. This research analyzes articles published in 2014-2024 to obtain an overview of the implementation of the tahfidzul qur'an program in schools. The results of the literature study show that the implementation of the tahfidzul Al Qur'an program in the context of school education can be carried out in various ways, namely habituation activities carried out every first hour before entering regular learning. Apart from that, tafidzul Qur'an can also be implemented in co-curricular programs as subjects in the regular curriculum which all students must follow. In another way, tahfidzul Qur'an can be programmed as an extracurricular activity that can be participated in by students who really need help in improving their ability to read the Qur'an. These programs can contribute to eradicating Qur'an illiteracy among students